PH-sensitive magnetic alginate/γ-Fe2O3 nanoparticles for adsorption/desorption of a cationic dye from water. (October 2018) - Talbot, Delphine; Abramson, Sébastien; Griffete, Nebewia; Bée, Agnès
Abstract: In this study, magnetic alginate nanoparticles (AlgMNP) were synthesized using a simple and green two-step method, which can be easily developed on an industrial scale. First, coprecipitation of both ferric and ferrous ions in alkaline medium followed by oxidation of magnetite into maghemite leads to a stable colloidal dispersion called ferrofluid. A sodium alginate solution was then added to the ferrofluid in order to obtain the magnetic nanocomposite. This approach combines the advantages of a biopolymer with magnetic properties of the maghemite nanoparticles. The morphology, structure, size and composition of the magnetic nanoparticles were characterized by means of atomic absorption spectrometry, transmission electron microscopy, X-ray diffraction, Fourier-transform-infrared spectroscopy and thermogravimetric analysis. Adsorption is one of the most efficient treatments for the removal of pollutants from wastewater. But the development of efficient and environmental friendly adsorbent still remains challenging. Using AlgMNP as a magnetic adsorbent could be a suitable response to this challenge. Its adsorption efficiency was investigated by using methylene blue as pollutant. The effects of pH, contact time, and initial concentration of the dye on adsorption were investigated. The high adsorption capacity with respect to the dye in a wide pH range (273 mg/g) was explained by the way magnetic nanoparticles bind to the alginate chains. We assumed an organization with alginate strands decorated by the magnetic nanoparticles leaving the adsorption sites of the particles more accessible rather than a configuration with a complete coating of magnetic nanoparticles by alginate. The reusability was successfully demonstrated through 10 adsorption/desorption cycles.